Role of Tau protein in long COVID and potential therapeutic targets - Marwaha, Bharat (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction: Long COVID is an emerging public health burden and has been defined as a syndrome with common symptoms of fatigue, shortness of breath, cognitive dysfunction, and others impacting day-to-day life, fluctuating or relapsing over, occurring for at least two months in patients with a history of probable or confirmed SARS CoV-2 infection; usually three months from the onset of illness and cannot be explained by an alternate diagnosis. Pathophysiology: Currently, there is limited understanding of the pathophysiology of this syndrome, and multiple hypotheses have been proposed. Our literature review has shown studies reporting tau deposits in tissue samples of the brain from autopsies of COVID-19 patients compared to the control group, and the in-vitro human brain organoid model has shown aberrant phosphorylation of tau protein in response to SARS-CoV-2 infection. Tauopathies, a group of neurodegenerative disorders with the salient features of tau deposits, can manifest different symptoms based on the anatomical region of brain involvement and have been shown to affect the peripheral nervous system as well and explained even in rat model studies. Long COVID has more than 203 symptoms, with predominant symptoms of fatigue, dyspnea, and cognitive dysfunction, which tauopathy-induced CNS and peripheral nervous system dysfunction can explain. There have been no studies up till now to reveal the pathophysiology of long COVID. Based on our literature review, aberrant tau phosphorylation is a promising hypothesis that can be explored in future studies. Therapeutic approaches for tauopathies have multidimensional aspects, including targeting post-translational modifications, tau aggregation, and tau clearance through the autophagy process with the help of lysosomes, which can be potential targets for developing therapeutic interventions for the long COVID. In addition, future studies can attempt to find the tau proteins in CSF and use them as biomarkers for the long COVID.